A completely digital approach to increase occlusal vertical dimension in centric relation for fixed full-mouth rehabilitation. (June 2022) - Feng, Yue; Liu, Weicai; Sun, Xinrong; Li, Yiyuan
Abstract : Purpose: Exactly recording centric relation(CR) and using this record to increase occlusal vertical dimension (OVD) safely is essential for fixed full-mouth rehabilitation. The present report describes a completely digital method to increase OVD in CR for fixed full-mouth rehabilitation. Methods: We obtained a digital intraoral impression and recorded patient-specific mandibular movements from open to close in a limited range(Within 5 mm approximately) with a jaw motion tracking system (MODJAW, France). And then the movements were replayed frame-by-frame extraorally, which assists to increase OVD straightforward in a virtual environment combined with the prosthetic requirement. And at the meantime, it is useful for determining an accurate CR by visualizing the hinge axis rotates without translation. The jaw relation in the new OVD can be exported directly and applied in dental cad software for digital waxing design or splint design. Results: This new approach digitizes the process of determining OVD, and contributes to the establishment of a completely digital workflow for fixed full-mouth rehabilitation. Conclusions: The present article describes a fully digital approach to increase OVD in CR for fixed full-mouth rehabilitation. By playing back mandibular movement extraorally, the clinician can determine the ideal mandibular position at desired OVD virtually and observe the condylar kinematics simultaneously. Besides, the new jaw relation can be digitally delivered to the dental laboratory for waxing design or splint design. It improves traditional methods, saves time, and reduces the complexity of full-mouth rehabilitation.